Antisense Phosphorodiamidate Morpholino Oligomers as Novel Antiviral Compounds - Nan, Yuchen; Zhang, Yan-Jin (Frontiers in Microbiology, 2018)
Phosphorodiamidate morpholino oligomers (PMO) are short single-stranded DNA analogs that are built upon a backbone of morpholine rings connected by phosphorodiamidate linkages. As uncharged nucleic acid analogs, PMO bind to complementary sequences of target mRNA by Watson–Crick base pairing to block protein translation through steric blockade. PMO interference of viral protein translation operates independently of RNase H. Meanwhile, PMO are resistant to a variety of enzymes present in biologic fluids, a characteristic that makes them highly suitable for in vivo applications. Notably, PMO-based therapy for Duchenne muscular dystrophy (DMD) has been approved by the United States Food and Drug Administration which is now a hallmark for PMO-based antisense therapy. In this review, the development history of PMO, delivery methods for improving cellular uptake of neutrally charged PMO molecules, past studies of PMO antagonism against RNA and DNA viruses, PMO target selection, and remaining questions of PMO antiviral strategies are discussed in detail and new insights are provided.